Analysis of the UNCITRAL Model Law on Cross-Border Insolvency and Its Potential Effectiveness in Indonesia - Panji Ahmad Setiawan; Imam Haryanto (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
Trade in the current era of globalization involves many countries around the world, both in bilateral and multilateral relationships. This has transformed trade from being limited to a single country into what is known as international business or international trade. With the rapid development of international business, various issues have emerged, including insolvency that involves more than one country with different jurisdictions, commonly referred to as cross-border insolvency. Currently, Indonesian law does not regulate this aspect, resulting in a legal vacuum regarding the execution of bankrupt assets outside Indonesia’s territory. This research employs a juridical-normative legal method with legislative and comparative approaches. Insolvency in Indonesia is governed by Indonesian Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. Under the principle of territoriality, bankruptcy rulings in Indonesia are only applicable within the national jurisdiction and lack enforceability abroad. This situation becomes complicated when a debtor who owes creditors from another country is declared bankrupt, or vice versa. One solution to address cross-border insolvency cases is to adopt the UNCITRAL Model Law on Cross-Border Insolvency, formulated by the United Nations, which aims to provide guidelines for resolving cross-border insolvency cases in various countries and to assist in handling such matters fairly and effectively.